A review of striking force in full-contact combat sport athletes: methods of assessment - Lenetsky, S.; Uthoff, A. M.; Coyne, J. O. C.; Cronin, J. B. (Strength and Conditioning Journal, 2022)
With striking force playing such a critical role in the success of full-contact combat sports such as mixed martial arts, taekwondo, and boxing, coaches and scientists must be able to track this performance metric accurately and reliably. This review will cover practitioner understanding of key kinetic variables used in the assessment of striking important concepts relating to the validity, reliability, and reporting of meaningful performance changes in the assessment process, a critique of the methods used to monitor changes in striking forces, and provide practical recommendations for practitioners in the field. This understanding will help coaches and scientists assess and interpret the effectiveness of training.